Estimation of Rupture Duration and Mwp Values to Identify Tsunami Generating Earthquakes in Northern Sulawesi - Muhammad Fikri Haykal Hiola; A. Nasrurroh (Himpunan Ahli Geofisika Indonesia (HAGI), 2019)
Sulawesi is an area that has a high potential for tsunamis, especially in the North Sulawesi region due to the presence of a Pundungan Mayu subduction resulting from a double collision between the Maluku Sea plate and Halmahera and Sangihe arcs. Analysis of the duration rupture and estimated Mwp has been carried out using the P-wave phase in the North Sulawesi region as one of the tsunami early warning parameters. The data used were teleseismic body wave (300-900) from three earthquake-generating earthquakes with magnitudes above 7 (Sulawesi earthquake November 16, 2008, Celebes earthquake February 11, 2009, Molucca earthquake November 15, 2014) taken from the IRIS waveform catalog with 90 stations BHZ component registrar. The wave used is the P-PP wave phase (20% -90%) with a high frequency bandpass (1-2 Hz) butterworth filter. The results of the duration of the rupture obtained for the Sulawesi earthquake, Celebes earthquake, Molucca earthquake respectively 53.72 s, 52.98 s, 52.50 s. Whereas for Mwp, it has conformity with Mw from the IRIS catalog. So it can be concluded that the tsunami-generating earthquake in Sulawesi has a duration of rupture greater than 50 s which can be categorized as tsunamigenic earthquake (> 50 s) and the use of Mwp can be applied. Keywords : rupture duration, tsunami, Northern Sulawesi, Mwp